Experimenting the human : art, music, and the contemporary posthuman - Barrett, G. Douglas (University of Chicago Press, 2023)
"In Experimenting the Human, G Douglas Barrett, himself an artist of experimental music, argues that a radical prefiguration of posthumanism can be found in the discourses and practices of postwar experimental music. Experimental music draws upon practices developed through exchanges between the US, Europe, and East Asia during the postwar era (along with influences from the pre-war avant-garde), including indeterminacy, open forms, and extended uses of music technology. Although not exclusively focused on technology, experimental music has played a critical role in shaping the fields of biofeedback, AI, and robotics-paradigms central to the development of cybernetics and, later, posthumanism. Beyond the modernist project of subjecting sound parameters to the deterministic human control exemplified by serialism, experimentalism has used indeterminacy-beginning with chance and natural processes and later incorporating computer algorithms, biofeedback, and AI-in ways that mirror posthumanism's challenge to the centrality of human agency. Through a series of six intimate studies of works by Alvin Lucier, Nam June Paik, Pamela Z, and Laetitia Sonami, Barrett places posthuman thought in dialogue with works of experimental music surveyed from the 1960s to the present. In addition to studies of individual musical works, he illustrates existing exchanges between experimental music and cybernetics theorists since the 1950s, and links this dialogue to posthumanist theory beginning in the 1990s for which those very cyberneticists were a primary point of departure. Posthumanism and experimental music address fundamental questions about the relationship between humans and technology and thus have much to learn from one another. This project illuminates the insights to be gained from viewing these two movements together. Experimental music can be informed by posthumanism's sustained inquiry into the relationship between the human and technology. Conversely, posthumanism, a field focused on literature and visual culture, may benefit from music that has worked through many of its essential concerns in practice"--